Study on the effect of inter-channel phase error in coherent beam combining of laser - Park, Jaedeok; Park, Sungmin; Choi, Dongwon; Yeom, Dong Il; Yu, Bong Ahn (Journal of the Korean Physical Society, 2024)
We study the impact of phase errors between channels on the beam-combining efficiency in a coherent beam-combining system. A tiled aperture beam-combining system with various output channel numbers ranging from 3 to 37 was experimentally implemented using a spatial light modulator and related optics. We then examined how the beam-combining efficiency changes when applying phase differences between channels for various output beam configurations. A Gaussian random phase was applied to each channel for 500 samples, and the intensity variation of the central part of the combined beam was monitored to examine the beam-combining characteristics in the presence of phase error. The experimental results show that as the standard deviation value of the phase distribution increases, the combined beam efficiency rapidly decreases for a given channel number. Furthermore, the beam-combining efficiency becomes more sensitive to phase errors as the number of combined channels increases. The beam-combining efficiency was maintained at 95% or higher when the phase error between channels was below 0.03λ. A numerical simulation was also conducted for the same output beam configuration, which agrees well with the results obtained from the experiment.
Keywords: Beam configuration; Channel number; Channel phase errors; Coherent beam combining; Combining efficiency; Combining systems; Output beam; Phase error; Spatial light modulators; Adaptive optics; Coherent beam combining; Spatial light modulator